SEJAUH MANA GURU MENGGUNAKAN METAFORA DALAM KEPEDULIANNYA UNTUK MENINGKATKAN KEMAMPUAN MATEMATIKA SISWA - Idrus Alhaddad (IKIP Siliwangi and I-MES, 2012)
Belajar matematika masih merupakan hal yang sulit bagi siswa, karena disamping memiliki objek kajian yang abstrak, juga berdasarkan pada pola pikir yang deduktif. Untuk membantu siswa dapat memahami bahkan menjadi senang dalam belajar matematika, hal ini tidak terlepas dari peranan guru. Bagi guru, memahami matematika juga merupakan hal yang sulit, dan lebih sulit lagi adalah mengajarkan kepada siswa untuk dapat dipahami. Karena hal itu membutuhkan strategi, metode, dan pendekatan. Dalam pembelajaran matematika banyak hal yang harus diperhatikan. Di antaranya adalah faktor-faktor yang mempengaruhi kegiatan belajar siswa yaitu: pengalaman, kemampuan, kematangan, dan motivasi siswa. Oleh karena itu, baik teori maupun metode dalam pembelajaran harus disesuaikan dengan kondisi siswa. Agar pembelajaran matematis menjadi bermakna dan dimaknai siswa, maka diperlukan cara-cara khusus untuk menjadikan siswa termotivasi belajar matematika. Salah satunya adalah penggunaan Metafora. Metafora dapat dipandang sebagai suatu strategi untuk membantu siswa dalam memahami matematika. Makalah ini akan menyajikan tentang apa sebenarnya metafofa, bagaimana menggunakannya dalam pembelajaran dan contoh penggunaannya serta kelebihan dalam menggunakan metafora Kata kunci : Kepedulian, Metafora, Pembelajaran Matematika Mathematics, for most of students, is still considered to be a difficult subject to learn because it does not only possess abstract objects of investigation but it is also based on deductive mindset. Enabling students to understand or even be enjoy learning mathematics, then, will demands good teachers’ roles. For teachers, understanding mathematics is also difficult as well. In fact, the most difficult thing for them is how to teach mathematics that can be easily and quickly understood by students. That is why; mathematics teachers need to use exact strategies, methods and approaches. In mathematics learning, there are many things to consider. One of which is factors influencing students’ learning activities, namely: their experience, ability, maturation, and motivation. That is why; we, as teachers, need to create learning methods and theories which are adaptive to students’ condition. In order to create meaningful mathematics learning which in turn students get the real meaning of it at last, then, we need to use special ways for enabling students to get motivated in learning mathematics. One of these ways is using metaphor. This can be considered as a strategy to help students understand mathematics. This paper will present about what metaphor really looks like, how to use it in learning activities; also, the examples of its use and the benefits we can get from using it in learning will be explained. Key Words: Concern, Metaphor, Mathematics Learning.